Uniqueness of Generalized Solutions for a Quasilinear Degenerate Parabolic System (Journal of Partial Differential Equations, 1995)
In this paper we study the uniqueness of generalized solutions for a class of quasilinear degenerate parabolic systems arising from dynamics of biological groups. The results obtained give an answer to a problem posed by A.S. Kalashnikov [1].
Keywords: Uniqueness; weak solution; quasilinear degenerate parabolic system